The Wreck of the Nancy Bell; Or, Cast Away on Kerguelen Land - Hutcheson, John C. (John Conroy); Stacey, W. S. (Walter S.), 1846-1929 (Salt Lake City, UT : Project Gutenberg, 2007)
"The Wreck of the Nancy Bell; Or, Cast Away on Kerguelen Land" by John Conroy Hutcheson is a nautical novel written in the late 19th century. The story revolves around the ill-fated voyage of the ship Nancy Bell as it sets sail from the UK to New Zealand, only to encounter a severe storm that leaves her crew and passengers struggling for survival after the ship becomes wrecked off the coast of Kerguelen Island. The narrative features a diverse cast of characters, including an ex-Royal Navy commander traveling in disguise and various sailors and passengers with their own distinct dialects. The opening of the novel introduces Captain Dinks and his crew aboard the Nancy Bell as they plan their course amidst challenging winds. A sense of camaraderie is established among the crew members, particularly between Captain Dinks and his first mate, McCarthy, as they manage the ship. Tension rises as the captain dismisses wise advice from the mysterious passenger, eventually leading to a disastrous storm that tests the resolve of everyone on board. The story begins to unfold with hints of conflict$1 (Bsuch as a brewing mutiny and mysterious occurrences aboard$1 (Bsetting the stage for the trials and tribulations that will follow the shipwreck and the survival challenge on Kerguelen Island. (This is an automatically generated summary.)s
Release date is 2007-04-15
Produced by Nick Hodson of London, England
Keywords: Sailors -- Fiction; Shipwrecks -- Fiction; Voyages and travels -- Fiction; Seafaring life -- Fiction; Castaways -- Fiction; Black people -- Fiction; Kerguelen Islands -- Fiction